Legal basises and protection of non-typical employment – a few dilemmas - Gersdorf, Małgorzata (The use of atypical forms of employment in violation of labour and social security laws - diagnosis and prospects for the future, 2023)
The analysis tends to predict the future of employment and the scope of subordination. It also underlines the need for research on the types of employment contracts.